Analysis of Spare Parts Inventory Control Using the Min-Max Stock Method and Continuous Review - Lailiyah, Wardatul; Pulansari, Farida; Dewi, Sinta (Journal La Multiapp, 2025)
Inventory is one component that has an important role in a company. The smooth production process and demand fulfillment will be greatly influenced by how to manage this component properly. PT XYZ, as one of the strategic power generation units in Indonesia, is responsible for providing a stable supply of electricity. As a company that relies on the reliability of machines and spare parts, good inventory management is essential. The problems faced include the inaccuracy in the procurement of spare parts which causes overstock or stockout with a range of around 10% to 20% which can disrupt the operation of the plant. improvements in inventory control are made using the Min-Max Stock and Continuous Review methods, both of which maintain a balance between inventory costs and spare parts availability to compare the smallest total inventory cost including ordering costs and storage costs. In addition, this research has novelty by providing recommendations for mitigating downtime risks to optimize spare parts inventory control in the power generation industry. Based on the results of the calculation of total inventory costs, the min max stock method is proven to be able to produce lower inventory costs and get savings of Rp 159.961.310 or around 25%. This efficiency proves that the application of Min-Max Stock can optimize spare parts inventory costs.